Reanimación cardiopulmonar-cerebral - Valenzuela W. , Germán; Chateau, María (Revista Hospital Clínico Universidad de Chile, 1996)
CARDIOPULMONARY AND BRAIN RESUSCITATION.The guidelines, recomendations and complications of cardiopulmonary and brain resucitation are analized.